Stenting of ruptured gastroduodenal artery pseudoaneurysm - Que, Do Kim; Tuong, Tran Quy (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Gastroduodenal artery (GDA) aneurysm is a rare surgical entity that causes various symptoms. In the case of rupture, it usually presents an ominous prognosis and mortality rate of up to 40%. Although open surgical procedure is a mainstay, endovascular intervention is emerging a promising treatment in recent years, due to its advantages and safety. We present a case of upper gastrointestinal bleeding caused by ruptured GDA pseudoaneurysmin a 71-year-old woman, with medical episodes of acute pancreatitis, a pancreatic body tumor removal surgery was performed, and now the tumor is relapsing and metastasizing. The treatment approach is blocking off the pseudoaneurysm by a covered stent. The procedure was successful and the patient is asymptomatic. Two months later, the pseudoaneurysm reduces its size and completely excluded from the preservation of the blood flow in the artery.Follow-up to 26 month, patient is well, no symptoms or recurrence. Endovascular interventional treatment in the case of GDA aneurysms is considered a promising alternative not only to open surgery but also to an effective emerging technique even in the acute setting. Keywords: Gastroduodenal artery - Covered stent - Aneurysm